Studi Kelayakan dan Persyaratan ruang shalat berdasarkan Syarat Ruang Shalat Dalam Islam Studi Kasus Masjid Al-Markaz Al-Islami Di Kabupaten Maros - Ansarullah Ansarullah; Muhammad Tayeb M (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2016)
With the development of human needs will either need relationships between fellow humans also need the human relationship with their Creator . Thus the need for action to review the main prayer hall as a function in terms of the requirements of Islamic worship space . The study was conducted at the Masjid Al Markaz Al Islami which is the main mosque , accommodating a variety of religious and social activities . Given the complexity of the space , is expected to fundamental provisions relating to the main function is not neglected , such as the sanctity of the place , the direction of Qibla , gender segregation , setting rows , mihrab and minbar , and other complementary devices prayer halls. There is a bit of a shortage on the aspects of the sanctity of the place that is the boundary between sacred and unclean areas are interpreted to provide the difference in color and texture of the floor , and height , visually still not sufficiently captured by the pilgrims . So also with aspects of setting rows are being a little more tenuous because of the existence of a rug with a pattern that sectional and acoustic space that still sounds echo , with a range that can be tolerated.